PENGARUH HASIL TES KEMAMPUAN INTELEKTUAL TERHADAP HASIL BELAJAR SENI RUPA SISWA DI MAN 2 PADANGSIDIMPUAN - SITI KHODIJAH LUBIS, Drs. Eswendi, M.Pd., Drs. Suib Awrus, M.Pd. (Universitas Negeri Padang, 2017)
This study aims to reveal the: (1) The effect of the results of tests of intellectual ability to the learning outcomes of art theory (2) The effect of the results of tests of intellectual ability to the learning outcomes of art practice, and (3) Effect of the results of tests of intellectual ability to the learning outcomes of art combined theory and practice of students MAN 2 Padangsidimpuan.The results showed the effect of intellectual ability test results: (1) the learning outcomes of students of art theory with determination coefficient of 0.903 or 90.3%, (2) to learn the art of practice areas has a coefficient of determination of 0.896, or 89.6%, and (3) the results of the combined fields studied art theory and practice fields students with determination coefficient of 0.943, or 94.3%.Keywords: Intellectual Ability Test Results, Results Learning Art